2014
DOI: 10.1002/cbic.201402443
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Gene Cluster CYP264B1‐geoA from Sorangium cellulosum So ce56: Biosynthesis of (+)‐Eremophilene and Its Hydroxylation

Abstract: Terpenoids can be found in almost all forms of life; however, the biosynthesis of bacterial terpenoids has not been intensively studied. This study reports the identification and functional characterization of the gene cluster CYP264B1-geoA from Sorangium cellulosum So ce56. Expression of the enzymes and synthesis of their products for NMR analysis and X-ray diffraction were carried out by employing an Escherichia coli whole-cell conversion system that provides the geoA substrate farnesyl pyrophosphate through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 99 publications
(127 reference statements)
0
43
0
3
Order By: Relevance
“…GC/MS analysis ( Figure S6 A) suggested the structure of valencene or eremo-philene,but it was not possible to clearly assign one of these structures.Alarge-scale incubation of 50 mg FPP yielded 4.6 mg (19 %) of the pure sesquiterpene with 1 H-and 13 C-NMR data matching those of eremophilene (2;T able S1). [21] Thep roposed biosynthesis of 2 (Scheme 3) starts with a1 ,10-cyclization of FPP to the (E,E)-germacradienyl cation J,f ollowed by deprotonation to germacrene A (K). [21] Thep roposed biosynthesis of 2 (Scheme 3) starts with a1 ,10-cyclization of FPP to the (E,E)-germacradienyl cation J,f ollowed by deprotonation to germacrene A (K).…”
Section: Methodsmentioning
confidence: 99%
“…GC/MS analysis ( Figure S6 A) suggested the structure of valencene or eremo-philene,but it was not possible to clearly assign one of these structures.Alarge-scale incubation of 50 mg FPP yielded 4.6 mg (19 %) of the pure sesquiterpene with 1 H-and 13 C-NMR data matching those of eremophilene (2;T able S1). [21] Thep roposed biosynthesis of 2 (Scheme 3) starts with a1 ,10-cyclization of FPP to the (E,E)-germacradienyl cation J,f ollowed by deprotonation to germacrene A (K). [21] Thep roposed biosynthesis of 2 (Scheme 3) starts with a1 ,10-cyclization of FPP to the (E,E)-germacradienyl cation J,f ollowed by deprotonation to germacrene A (K).…”
Section: Methodsmentioning
confidence: 99%
“…During our recent investigations on P450 enzymes from the myxobacterium Sorangium cellulosum So ce56, several interesting enzymes displaying new properties and substrate specificities have been discovered, which lead us to investigate the potential of these P450 enzymes for an application as drug metabolizing biocatalysts Schifrin et al, 2015;Litzenburger and Bernhardt, 2016). Therefore, we used bioinformatics analysis to identify myxobacterial P450 enzymes that are closely related to drug metabolizing P450 enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the strain Sorangium cellulosum So ce56 contains 21 P450s, 8 ferredoxins, and 2 ferredoxin reductases . However, only seven of the P450s, belonging to families CYP109 (CYP109C1, CYP109C2, and CYP109D1) , CYP264 (CYP264A1 and CYP264B1) , and CYP267 (CYP267A1 and CYP267B1) , were well characterized either for potential physiological or biotechnological applications. They are involved in the hydroxylation of fatty acids, terpenes, and terpenoids, as well as of drugs and drug derivatives .…”
mentioning
confidence: 99%